Evaluasi Kinerja Aparatur Pemerintahan Desa Berbasis Islamic Human Resource Management dalam Mewujudkan Tata Kelola Desa Digital di Era Society 5.0 - Alvin Dian Pramuja; Zakky Zamrudi; Syahrial Shaddiq (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the performance evaluation system of village government officials based on the principles of Islamic Human Resource Management (IHRM) in the context of transformation towards digital village governance in the era of Society 5.0. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation of the Karang Sari Village Government apparatus, Kusan Hulu District, Tanah Bumbu Regency. The results show that the village apparatus performance evaluation system is still administratively oriented and does not fully reflect the principles of justice, trustworthiness, and ihsan as Islamic values. However, there are efforts to strengthen accountability and digitization through the implementation of an online performance reporting application. The discussion of this study emphasizes that the application of IHRM can strengthen the integrity of officials while increasing transparency and performance efficiency in digital village governance. The conclusion of the study shows that the integration of Islamic values with digital technology can create an evaluation system that balances spiritual and professional dimensions, supporting the realization of a competitive village administration in the Society 5.0 era.